Research on water treatment / Nurzawani Md Sofwan ... [et al.] - Md Sofwan, Nurzawani; Budin, Hemyza; Abd Rashid, Ahmad Faiz; Mohd Anas Khan, Mohd Yazid; Yusuf, Nur Afisha; Abu Bakar, Nur Ain; Emeih Wahed, Wan Juliana; Bohari, Asmah Alia; Morni, Affidah; Johari, Aiza; Perreau, Madeleine Elna (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
The findings from the research are proposed to be expanded and applied to the river rehabilitation projects for Sarawak rivers. The project is still at the proposal stage, and the researchers have already presented it to the representatives of the Sarawak State Government for approval.